2022
DOI: 10.1155/2022/2822171
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Task Balance Training for Motor Skill Development among Children with Intelligence Quotient Discrepancy

Abstract: The motor skills of people with mental disabilities are reportedly reduced compared with those of their peers. Therefore, any task incorporating both motor and cognitive skills was hypothesized to provide better motor recovery. The aim of this study is to find the effect of dual-task balance training (DTBT) on motor skill development in children of 6–13 years with intelligence quotient discrepancy (IQD) (score: 50–79). Overall, 30 individuals with mental disabilities aged 6–13 years having an IQ score of 50–79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The findings support prior research which found significant impact of a dual task activity programme on balance for developmental coordination disorder children in age group of 7 to 9 years 11 . A study conducted to improve motor skills in Intelligence Quotient (IQ) discrepancy children aged 6 to 13 years reported that dual task activity had more effect than standard balance training 12 . A case study on task-oriented approach for balance, mobility, coordination and speed for upper-lower extremity and strengthening was conducted and showed significant improvement 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings support prior research which found significant impact of a dual task activity programme on balance for developmental coordination disorder children in age group of 7 to 9 years 11 . A study conducted to improve motor skills in Intelligence Quotient (IQ) discrepancy children aged 6 to 13 years reported that dual task activity had more effect than standard balance training 12 . A case study on task-oriented approach for balance, mobility, coordination and speed for upper-lower extremity and strengthening was conducted and showed significant improvement 7 .…”
Section: Discussionmentioning
confidence: 99%
“…MR may have a strong therapeutic interest for this population because it can provide cognitive, perceptive, and motor stimulation for the user. Perceptual-motor training can improve motor skills in either healthy or pathological populations [ 27 , 28 , 29 , 30 ] and motor training can improve cognitive abilities [ 9 ]. Furthermore, extended reality technologies such as VR or MR allow for immersive and playful activities.…”
Section: Introductionmentioning
confidence: 99%